This use of the rule is incorrect,
First, I multiplied both sides by dn : dn = N0/N
Then I took the log of both sides: n log d = log(N0/N)
Finally, I divided both sides by log d: n = log(N0/N)/log d
Does this look legit?
I was thinking of using the division log rule to manipulate it further: n = log(N0/N)-log d
Is this correct?
Sorry, I typed the original post using Word with super and subscripts and copied/pasted it to the page....apparently the super/subscripts didn't transfer over. N0 is N subzero...
So, the original expression should've read:
N = N0/d^n
1. I first isolated d^n to give: d^n = N0/N
2. Then I took the log of both sides: n*log d = log (N0/N)
3. And then divided both sides by log d: n = log(N0/N)/log d